Analisis Implementasi Kebijakan Pendayagunaan Sumber Daya Manusia Kesehatan di Puskesmas Daerah Tertinggal, Perbatasan, dan Kepulauan (DTPK) - Putro, Gurendro; Barida, Iram (Media Penelitian dan Pengembangan Kesehatan, 2018)
The availability of health workers in the public health center (puskesmas) in underdeveloped,borders, and islands region (DTPK) areas is very diverse both in number and type. This studyaimed to analyze implementation of government policy towards the utilization of health humanresources based on competence and incentive in DTPK area. This research was cross sectionalstudy, the primary data was collected by interview to respondents and the secondary data was frompuskesmas reports and district health profiles. Research was conducted for 10 months startingfrom January to October 2011. This research was performed in 4 districts, which were Natuna,Nunukan, Sangihe Island, and Belu. The availability of the number and types of health personnelat DTPK health center were currently not in accordance to the ideal requirements of the Ministry ofHealth policy on the placement of health human resources at the DTPK health center. Competenceof health personnel at DTPK health center was still the basic competence of science accordingto the type of education. The placement of health personnel needs to obtain additional specialcompetencies tailored to the characteristics of the DTPK Puskesmas. The incentives of PTT healthworkers and special assigment is higher compare to the civil servant at DTPK area.AbstrakKetersediaan tenaga kesehatan di puskesmas Daerah Tertinggal, Perbatasan, dan Kepulauan(DTPK) sangat beragam baik jumlah dan jenisnya. Tujuan penelitian adalah menganalisisimplementasi kebijakan pemerintah berkaitan dengan penentuan standar sumber daya manusia(SDM) kesehatan berbasis kompetensi dan pemberian insentif tenaga kesehatan di puskesmasDTPK. Jenis penelitian cross sectional, pengumpulan data primer dengan wawancara kepadaresponden dan data sekunder dari laporan puskesmas dan profil kesehatan kabupaten. Waktupenelitian selama bulan Januari-Oktober 2011. Lokasi penelitian di Kabupaten Natuna, KabupatenNunukan, Kabupaten Kepulauan Sangihe, dan Kabupaten Belu. Ketersediaan jumlah dan jenistenaga kesehatan di puskesmas DTPK saat ini belum sesuai dengan syarat ideal kebijakanKementerian Kesehatan RI tentang penempatan SDM kesehatan di puskesmas DTPK. Kompetensitenaga kesehatan di puskesmas DTPK masih bersifat kompetensi dasar keilmuan sesuai jenispendidikan. Penempatan tenaga kesehatan perlu mendapatkan tambahan kompetensi khususyang disesuaikan dengan karakteristik di puskesmas DTPK. Insentif yang diterima petugaskesehatan PTT lebih tinggi dibandingkan dengan gaji yang diterima oleh petugas PNS Puskesmas.